2010
DOI: 10.1016/j.drugalcdep.2009.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine use, aggressive behavior and other mental health issues among high-school students in Cape Town, South Africa

Abstract: Objective Methamphetamine use has become a growing problem in a number of countries over the past two decades, but has only recently emerged in South Africa. This study investigated the prevalence of methamphetamine use among high-school students in Cape Town and whether students reporting methamphetamine use were more likely to be at risk for mental health and aggressive behavior problems. Method A cross-sectional survey of 15 randomly selected high-schools in Cape Town, of 1561 male and female grade 8–10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 25 publications
8
87
0
Order By: Relevance
“…Only few studies have reported the extent of substance use among diverse adolescent populations (e.g., Ghana [13,14,15]; South Africa [16,17,18]; Zambia [19]; Zimbabwe [20]. A recent transnational study investigating the prevalence of marijuana and amphetamine use, and associated risk factors among adolescents in 9 African countries found overall past month marijuana use among school going adolescents to be 4.1% [21].…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have reported the extent of substance use among diverse adolescent populations (e.g., Ghana [13,14,15]; South Africa [16,17,18]; Zambia [19]; Zimbabwe [20]. A recent transnational study investigating the prevalence of marijuana and amphetamine use, and associated risk factors among adolescents in 9 African countries found overall past month marijuana use among school going adolescents to be 4.1% [21].…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine (MA) abuse and dependence are significant public health problems both in the United States (Gonzales et al, 2010) and worldwide (Pluddemann et al, 2010;Rawson and Condon, 2007; United Nations Office on Drugs and Crime, 2009;Wechsberg et al, 2010). Behavioral treatments, such as cognitive behavioral therapy, are the principal therapeutic strategy used for MA dependence, but they have only achieved modest success (Lee and Rawson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The drug is commonly used by young people of mixed ancestry, [2] and particularly those of lower socioeconomic status and educational level. [3] A closely related amphetamine, known as Ecstasy, was initially used as an appetite suppressant but rapidly became a recreational drug used in dancing clubs, where it was found to cause hyperthermia, dehydration and rhabdomyolysis, and an increased risk of acute renal failure. [4] Methamphetamine is relatively easy and inexpensive to produce, making it readily accessible.…”
mentioning
confidence: 99%